Perlindungan Hukum Terhadap Konsumen Terkait Penjualan Makanan Dan Minuman Dalam Kemasan Kadaluarsa - Hatu, Mohamad. Akbar R.; Dungga, Weny Almoravid; Mustika, Waode (CV. ITTC INDONESIA, 2023)
Abstract In the current era of globalization and technological development, many Indonesian industries are competing to produce goods, including food and beverages, which are continuously developing rapidly, therefore consumers must be more careful in choosing food and beverage products that are circulated and marketed in Indonesia. Food and beverage production that is marketed only becomes the object of exploitation by business actors who deliberately seek profit because of the reality at this time there are still many consumers who only directly accept and consume food and beverage products that are circulated and marketed without paying attention to the dangers of consuming them, food ingredients and beverages are commodities that are utilized for the survival of society in general. i This research uses normative juridical methods, namely research sources from books, papers, journals, i internet and other sources.i According to Article 19i of Law Number 8i Year 1999i concerning Consumer Protection, i Business actors are responsible for providing compensation for damages, pollution and/or losses to consumers as a result of consuming goods and/or services produced/traded. i Fostering and Supervision of Food and Beverage Distribution by BPOM i standardization which is the function of setting standards, i regulations, and policies related to the supervision of Food and Drug Administration.